TYPES AND SPECIAL FEATURES OF BANK CREDITS (Conferencea, 2021)
Credit relations are an integral part of a market economy and can be described as a process of buying and selling money in a simplified version. The essence of lending is the mandatory return of free funds to the lender, the movement of funds to the borrower on the basis of a limited period of use of funds in a timely manner and payment, the calculation of interest in favor of the lender. In a market economy, many types of financial services are included in the definition of credit relationships - leasing, banking, factoring, loans, microcredit and much more. The following article looks into the types of credits.